2009
DOI: 10.1007/s10530-009-9467-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of parasite release in invasion of the USA by European slugs

Abstract: Several species of European slugs are invasive in the USA, threatening native species and damaging agricultural and horticultural crops. One possible explanation for the success of these invaders is parasite release. To test this hypothesis we collected European slugs in part of their native range (United Kingdom) and in the USA and compared prevalence, distribution and species richness of their nematode parasites. All slugs were dissected and examined for the presence of nematodes. In the UK, nematodes were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…MacLeod et al 2010;Mitchell and Power 2003;Ross et al 2010). Table 1 versus the mean number of these native parasites recorded per population in the introduced range, and their relationships according to linear regression (species: R 2 = 0.23, F 1,5 = 1.50, P [ 0.05); genus: R 2 = 0.16, F 1,5 = 1.01, P [ 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MacLeod et al 2010;Mitchell and Power 2003;Ross et al 2010). Table 1 versus the mean number of these native parasites recorded per population in the introduced range, and their relationships according to linear regression (species: R 2 = 0.23, F 1,5 = 1.50, P [ 0.05); genus: R 2 = 0.16, F 1,5 = 1.01, P [ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Torchin and Mitchell (2004) suggested that when a species is introduced, it escapes at least 75 % of their parasites from their native range and thus will gain substantial benefits regarding their fitness and survival in the invasive range (Torchin et al 2003). The enemy release hypothesis has been used as the basis to explain the invasion success of a diverse range of species, including non-native slugs (Ross et al 2010), mosquitoes (Aliabadi and Juliano 2002) and frogs (Marr et al 2008). In fish, for two introduced fish species (Apollonia melanostoma and Proterorhinus semilunaris) in the North American Great Lakes, parasite diversity in both species was considerably lower than their native range, despite them also being present for approximately 100 years (Kvach and Stephien 2008).…”
Section: Introductionmentioning
confidence: 99%
“…parasitising slugs in the UK To investigate relationships between nematodes and temperature under field conditions, data from an October 2005 study of parasites in slugs in the UK were re-examined. The host association data have been published previously but did not take into account potential climate effects on parasitism (Ross et al 2010a) or prevalence of parasites at sampled sites. For the current study, we analysed the eight sites at which Phasmarhabditis spp.…”
Section: Reproductive Potential Of P Hermaphrodita At Different Tempmentioning
confidence: 99%
“…In the absence of commercial application, it is likely that P. hermaphrodita exerts natural control on slugs in its European home range as it is common and widespread ). However, three fairly widespread searches in the USA failed to find P. hermaphrodita or any other slugparasitic member of the genus Phasmarhabditis (Grewal et al 2000;Kaya and Mitani 2000;Ross et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to advantages A. rufus has in its non-native range which the species does not have in its native range, such as release from nematodes as has been shown for several species of the genus Arion (Ross et al 2010). In addition, it also could be that A. rufus belongs to a cryptic species complex which includes forms/species differing in their invasion potential as has recently been shown for the complex Arion subfuscus/fuscus (Pinceel et al 2004).…”
Section: Discussionmentioning
confidence: 99%